EFEKTIFITAS PERAN PEMERINTAH DALAM BERKONTRIBUSI PADA PEMBANGUNAN DAERAH - RIZKIA ZAHRA; KHAIRANI TAMBUNAN (JURNAL ILMIAH MAKSITEK, 2021)
The main task of the daerh government in the era of autonomy daereah is very important. Where the local government isgiven special power broadly to be able to take care to help the central government in empowering the potential of the area.To be able to carry out this task, the Government should play an active role in the economic development of its regions.There are many obstacles that are often faced by local governments in their economic development, namely the overridmentof industrial sector development. Less equitable uvestation, low level of mobility factor production and differences in naturalresources. These problems cause an impact on the economic development of the region which will remain a persistentproblem. The extortion can be above with various strategies according to experts in solving the problem. In the opinion ofArsyad (2000) there is a physical development strategy, business development strategy, business development strategy,community development strategy, these strategies are at least helpful or one of the references for local governments inovercoming problems in their regional economic problems so that economic development can run well, economic growthincreases and community income also increases.